Phase II Study of Taselisib in PIK3CA-Mutated Solid Tumors Other Than Breast and Squamous Lung Cancer: Results From the NCI-MATCH ECOG-ACRIN Trial (EAY131) Subprotocol I. (9th February 2022) - Krop, Ian E.; Jegede, Opeyemi A.; Grilley-Olson, Juneko E.; Lauring, Josh D.; Mitchell, Edith P.; Zwiebel, James A.; Gray, Robert J.; Wang, Victoria; McShane, Lisa M.; Rubinstein, Larry V.; Patton, David; Williams, P. Mickey; et al.
Abstract : PURPOSE: PIK3CA mutations frequently contribute to oncogenesis in solid tumors. Taselisib, a potent and selective inhibitor of phosphoinositide 3-kinase, has demonstrated clinical activity in PIK3CA -mutant breast cancer. Whether PIK3CA mutations predict sensitivity to taselisib in other cancer types is unknown. National Cancer Institute–Molecular Analysis for Therapy Choice Arm EAY131-I is a single-arm, phase II study of the safety and efficacy of taselisib in patients with advanced cancers. METHODS: Eligible patients had tumors with an activating PIK3CA mutation. Patients with breast or squamous cell lung carcinoma, or whose cancer had KRAS or PTEN mutations, were excluded. Patients received taselisib 4 mg, orally once daily continuously, until disease progression or unacceptable toxicity. The primary end point was objective response rate. Secondary end points included progression-free survival (PFS), 6-month PFS, overall survival (OS), and identification of predictive biomarkers. RESULTS: Seventy patients were enrolled, and 61 were eligible and initiated protocol therapy. Types of PIK3CA mutations included helical 41 of 61 (67%), kinase 11 of 61 (18%), and other 9 of 61 (15%). With a median follow-up of 35.7 months, there were no complete or partial responses. Six-month PFS was 19.9% (90% CI, 12.0 to 29.3) and median PFS was 3.1 months (90% CI, 1.8 to 3.7). Six-month OS was 60.7% (90% CI, 49.6 to 70.0) and median OS was 7.2 months (90% CI, 5.9 to 10.0). Individual comutations were too heterogeneous to correlate with clinical outcome. Fatigue, diarrhea, nausea, and hyperglycemia were the most common toxicities, and most were grade 1 and 2. CONCLUSION: In this study, taselisib monotherapy had very limited activity in a heterogeneous cohort of heavily pretreated cancer patients with PIK3CA -mutated tumors; the presence of a PIK3CA mutation alone does not appear to be a sufficient predictor of taselisib activity.